2021
DOI: 10.3390/pharmaceutics13020204
|View full text |Cite
|
Sign up to set email alerts
|

A Physiologically-Based Pharmacokinetic Framework for Prediction of Drug Exposure in Malnourished Children

Abstract: Malnutrition in children is a global health problem, particularly in developing countries. The effects of an insufficient supply of nutrients on body composition and physiological functions may have implications for drug disposition and ultimately affect the clinical outcome in this vulnerable population. Physiologically-based pharmacokinetic (PBPK) modeling can be used to predict the effect of malnutrition as it links physiological changes to pharmacokinetic (PK) consequences. However, the absence of detailed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…Verified PBPK models of drugs are presented in support of pediatric dose prediction (Figure 4 ): 13 articles reported results from P‐PBPK models, which are presented in support of dose selection, 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 five articles were on the optimization of dosage in the design of future pediatric clinical studies, 3 , 29 , 43 , 44 , 45 and six articles reported findings from studies on determining dose regimens. 46 , 47 , 48 , 49 , 50 , 51 Fourteen publications were on some special pediatric populations and uncommon diseases with an assessment of renal impairment, 52 , 53 , 54 , 55 , 56 children with obesity, 57 , 58 , 59 , 60 and pediatric patients with severe coronavirus disease 2019 (COVID‐19) disease. 61 , 62 , 63 , 64 , 65 Consistent with this trend, several big research funding/grants for computational pharmaceutics worldwide were launched (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Verified PBPK models of drugs are presented in support of pediatric dose prediction (Figure 4 ): 13 articles reported results from P‐PBPK models, which are presented in support of dose selection, 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 five articles were on the optimization of dosage in the design of future pediatric clinical studies, 3 , 29 , 43 , 44 , 45 and six articles reported findings from studies on determining dose regimens. 46 , 47 , 48 , 49 , 50 , 51 Fourteen publications were on some special pediatric populations and uncommon diseases with an assessment of renal impairment, 52 , 53 , 54 , 55 , 56 children with obesity, 57 , 58 , 59 , 60 and pediatric patients with severe coronavirus disease 2019 (COVID‐19) disease. 61 , 62 , 63 , 64 , 65 Consistent with this trend, several big research funding/grants for computational pharmaceutics worldwide were launched (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reason is that food increases the secretion of bile salts that will improve the absorption of these lipophilic drugs. The bioavailability of lumefantrine in fasted or malnourished children may be as low as 4.7% [65]. Other influencing factors in malnourished children are the villous atrophy as well as the reduced bile salt concentration secreted into the duodenum.…”
Section: Pharmacokinetic Methodsmentioning
confidence: 99%
“…Demographic data on heights and weights of children in African regions were collated from literature [22][23][24] and used to generate the appropriate heights and weights of virtual subjects in the pediatric simulations (Figure 2). Comprehensive measurements of plasma albumin in pediatrics reported previously, 25 which are in concordance with reduced levels of albumin in subjects with mild/severe chronic undernutrition 26 and modeling drug exposure in malnourished children, 27 were used to derive the ontogeny function of albumin levels in the African pediatric population. The equations for heights, weights, albumin, and CYP ontogeny are provided in the Supplementary Material S1.…”
Section: Virtual Populationsmentioning
confidence: 99%